Tinjauan Teologi Pelayanan Perempuan - Sarah Wassar (Jurnal Apokalupsis, 2021)
In teological perpective, women ministry herewith explains that women are called to serve God as well. A biblical study underlies woman ministry in family, churches and soceity. Therefore, women will not be binded to the cultural rules or patriachy system which contradics the Bible, that has been believed by the soceity and churches for years. Furthermore, The biblical truth of minister God will set women free to serve God.